2011
DOI: 10.1021/mp2001268
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Electrostatically Coated with Folic Acid for Effective Gene Therapy

Abstract: We developed a novel vector, electrostatically coated poly(ethylenimine) (PEI)/pDNA complexes with folic acid (FA). Without covalent binding, the FA molecules could coat the PEI/pDNA complexes, and stable anionic nanoparticles were formed at a charge ratio greater than 60. The addition of FA markedly decreased the cytotoxicity of the cationic PEI/pDNA complexes to the melanoma cell line, B16-F10 cells, which regularly expressed FA-specific receptor (FR). Furthermore, the anionic FA60/PEI/pDNA complexes showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Some researchers reported that anionic charged gene vector modified with anionic ligands such as hyaluronic acids (HA) and folic acid (FA) showed high transgene expression. 18,19) These vectors were taken up by HA or FA receptor-mediated endocytosis. The anionic pDNA/PEI/DOPS complex also may be specifically taken up via a DOPS-related pathway although further studies are necessary to confirm the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reported that anionic charged gene vector modified with anionic ligands such as hyaluronic acids (HA) and folic acid (FA) showed high transgene expression. 18,19) These vectors were taken up by HA or FA receptor-mediated endocytosis. The anionic pDNA/PEI/DOPS complex also may be specifically taken up via a DOPS-related pathway although further studies are necessary to confirm the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These transfection efficiencies were as great as the commercially available transfection reagent, lipofectin (1.49×10 8 RLU/mg protein). 23) This high gene expression of pDNA/ protamine6.4 must be explained by interaction of cationic protein with a negative charge cellular membrane. 24,25) On the other hand, the morphology of pDNA condensates may be important for gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, amiloride, chlorpromazine, and geneistein can inhibit macropinocytosis and clathrin-mediated and caveolae-mediated endocytosis, respectively. 24 To compare the endocytotic pathway of PPG1 supermolecule/pDNA polyplex and PEI 25K/pDNA polyplex in HEK293A cells, the cells were pretreated with 1.0 mM amiloride, 0.014 mM chlorpromazine, 0.2 mM genistein, or coinhibitors (0.014 mM chlorpromazine and 0.2 mM genistein) for 1 h before transfection. The PPG1 supermolecule/pDNA polyplex at the weight ratio of 5 and PEI 25K/pDNA polyplex at the N/P ratio of 10 containing 1.0 μg of pDNA were added to cells in the presence of the inhibitors according to the transfection experiment mentioned above.…”
Section: Characterization Of Ppg1 Supermoleculs and Ppg1mentioning
confidence: 99%